Genetic origins and migration patterns of Xinjiang Mongolian group revealed through Y-chromosome analysis - Wang, Yifan; Xie, Lei; Wang, Ke; Jiang, Zixi; Feng, Yuhang; Yu, Yao; Chang, Xin; Meng, Hailiang; Xu, Yiran; Wu, Yishan; Shi, Meisen; Wang, Xiaoxia; et al. (Frontiers in Ecology and Evolution, 2024)
The Xinjiang Mongolians, located along the Silk Road, migrated westward from Northeast Asia in the 13th and 14th centuries. Despite its significance, genetic studies on Xinjiang Mongolians have been limited compared to other Mongolian populations. In this study, we analyzed the non-recombining region of the Y-chromosome in 165 Xinjiang Mongolian males using 108 biallelic markers and 44 STRs. Our study identified prevalent haplogroups C2a1a3-F1918 (10%), C2a1a2-M48 (8%), N1a1a-M178 (5%), and R1a1a-M17 (10%) in the Xinjiang Mongolians . Additionally, our study suggested a genetic affinity between Xinjiang Mongolians and Inner Mongolia Mongolian populations, as well as other ethnic groups from northwest China, based on the PCA analysis. The Network analysis revealed distinct branching expansion patterns in haplogroups C2a1a3a-F3796, C2a1a2-M48, and N1a1a-M178, with estimated timeframes aligning with Genghis Khan's invasion of Xinjiang in the Yuan Dynasty. Notably, our analysis of the R1a1a-M17 Network highlighted the role of Xinjiang Mongolians in the expansion of Turkic-speaking populations in Xinjiang and surrounding regions. The integration of ancient DNA data suggested that the high frequency haplogroups C2a1a3a-F3796, C2a1a2-M48, and N1a1a-M178 could be traced back to their origin in Northeast Asia. Furthermore, the estimated TMRCA of haplogroup R1a1a-M17 implied cultural and genetic influences from Turkic populations during the Qagatay Khanate period. Overall, our study provided a genetic explanation for the ethnic origin of Xinjiang Mongolians, highlighting their migration from Northeast Asia and subsequent assimilation with the local populations in Xinjiang.